An overview of surgical treatment modalities and emerging transcatheter interventions in the management of tricuspid valve regurgitation. (1st February 2018) - Van Praet, Karel M.; Stamm, Christof; Starck, Christoph T.; Sündermann, Simon; Meyer, Alexander; Montagner, Matteo; Nazari Shafti, Timo Z.; Unbehaun, Axel; Jacobs, Stephan; Falk, Volkmar; Kempfert, Jörg
ABSTRACT: Introduction : Tricuspid valve regurgitation (TR) is frequently encountered and is most often functional (FTR) in nature. Surgical tricuspid valve (TV) treatment is well established in specialized centers. While transcatheter therapy for other valve disease is well established, interventional treatment of TV disease is still in its early stages. With the increasing adoption of catheter-based treatments, there is a growing interest in and need for interventional treatments for TR. An extensive literature search was methodologically performed aiming for an integrative review paper. Areas covered : This review will discuss the current surgical treatment modalities and emerging transcatheter interventions in the management of TR. Furthermore, this review will describe the pathophysiology of functional tricuspid regurgitation (FTR), and the new 2017 ESC/EACTS guidelines for the management of TR. Finally, a five-year view into the future will be stated. Expert commentary : At their center, the authors have an aggressive approach for the treatment of FTR owing to its significant impact on perioperative as well as late postoperative morbidity and mortality. The authors perform TV ring annuloplasty when substantial annular dilation (≥45mm) is observed. In the future, percutaneous TV technologies might become an alternative option to treat TR patients with high surgical risk selectively.